The study of Qarakhanid-Chinese relations in foreign English-language historiography (2000-2022) - Almagambetova Алия (Turkic Studies Journal, 2023)
The article is devoted to a historiographical review of the works of modern foreign authors on the problems of Qarakhanid-Chinese relations. The author of the article has studied the works of the last twenty years published in reputable foreign editions. Such works include scientific articles, monographs written in English. The purpose of this article is to analyze the problems in the study of interstate relations between the Qarakhanid State and the Chinese Empire in the Late Middle Ages. The author of the article managed to highlight the main issues of the Turkic-Chinese relations considered by foreign authors. The main methods used are general scientific methods, as well as comparative, historical and genetic methods and critical types of analyses. As a result of the conducted research, the following results were obtained: Chinese sources confirm the information that was presented in the Arab-Persian sources and do not contribute more detailed or new information to the study of this issue. Moreover, there are a number of issues in these Qarakhanid-Chinese relations that require further research. Of particular interest is the question of gifts and goods that circulated between States, through which the essence and purpose of the desired relations are also manifested. A certain list of gifts or goods and their purpose demonstrate the nature of the relations between the Parties, which in turn affects the further course of events. The analyzed English-language works can be used in the study of the problems of the foreign policy of the Qarakhanid State, in the study of the trade routes of the Great Silk Road and in the analysis of the role of the Qarakhanids between the Muslim and Chinese worlds.